Positivism or understanding? The complexity of analyzing the objectives of armed opposition groups - Ylönen, A. (Critical Review, 2021)
The analysis of armed opposition groups is heavily tainted by gross categorizations and labeling. Using vague terms that reduce the objectives of such groups to a uniform binary of secessionist or reformist defies their ideational complexity, undermining the effort to gain a nuanced and in-depth understanding of their actual motives. A closer look into the Ogaden National Liberation Front in Ethiopia reveals the type of complexity we might expect to find in armed opposition groups’ objectives, and thus the problem with superficially labeling them to make for easy comparative analyses.